Design Principles for a Family of Direct-Drive Legged Robots - Kenneally, Gavin; De, Avik; Koditschek, D. E. (IEEE robotics and automation letters, 2016)
This letter introduces Minitaur, a dynamically running and leaping quadruped, which represents a novel class of direct-drive (DD) legged robots. We present a methodology that achieves the well-known benefits of DD robot design (transparency, mechanical robustness/efficiency, high-actuation bandwidth, and increased specific power), affording highly energetic behaviors across our family of machines despite severe limitations in specific force. We quantify DD drivetrain benefits using a variety of metrics, compare our machines' performance to previously reported legged platforms, and speculate on the potential broad-reaching value of "transparency" for legged locomotion.